The Training in Early Fire Fighting Using Portable Fire Extinguishers at Penjaringan Sari, Surabaya - Indri Santiasih; Dika Rahayu Widiana; Ryan Yudha Aditya; Adhi Setiawan; Vivin Setiani; Suci Indaryani; Yoga Dwikurniawan; Vanny Nastiti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Surabaya is currently in an urban development phase. This is indicated by the increasing population growth every year. According to data from Badan Pusat Statistik (BPS) in 2021, the population of Surabaya was approximately 2880284 people. The population density in Surabaya was around 8612 people per square kilometer. This number increased by 0.28 % from 2020 to 2021. The land conversion from open land to residential land in Surabaya thus increased population density. The high density of residential areas had a greater likelihood of fire hazards that were more difficult to control. It happened because they facilitated the rapid propagation of fire. In addition, the high temperature in Surabaya ranging from 22oC – 34oC was a factor that triggered fire as well. Furthermore, various activities also produced potential hazards including the leakage of LPG gas, electrical short circuits, and the residents' habit of throwing cigarette butts, coupled with the low fire safety system in buildings and the community’s lack of ability to prevent and overcome light fire. So, this was a factor that exacerbated the incidents of fires in residential areas. Therefore, the training and simulation activities of early firefighting using portable fire extinguishers aimed to provide the understanding and skill of Penjaringan Sari residents in the ignition phase of the fire. This was the way to prevent large fires. A portable fire extinguisher (PFE) was easy to use by residents for early fire fighting. The results of the training and simulation showed that there was an increase in the knowledge of the people of Kelurahan Penjaringan Sari about the material of the fire and its management. This was demonstrated by an increase in the number of correct answers in 95.5% of respondents based on pre-test and post-test results.